1993
DOI: 10.1080/02772249109357906
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of organochlorine pesticides in a tropical waterway: HCH isomers

Abstract: Pesticide residue levels in the aquatic systems are scattered and fragmentory in India. A systematic analysis of the distribution pattern of the common organochlorine pesticide Hexachlorocyclohexane (HCH) and its isomers in the waters of the tropical positive estuarine system (the Cochin Estuarine System) has been carried out for the first time. The average concentrations of HCH ranged between 0.013 and 1.125 µg 1 -1 . α-HCH was found to be at an appreciable concentrations throughout the study area and formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Previously, Mathur (1993), reported that, around 25,000 MT (metric tons) of chlorinated pesticides were used annually in India and DDT accounted for 40% of this group. Among the HCH isomers, a-HCH is more likely to diffuse into the air and get transported for a long distance, while b-HCH is more resistant to hydrolysis and environmental degradation, and is the predominant isomer in the water, fluids, animal tissues and sediments (Sujatha et al, 1993;Walker et al, 1999;Lee et al, 2001). In the present research work, total HCH concentration of 423 ng/g was detected in the entire study area during 2009.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previously, Mathur (1993), reported that, around 25,000 MT (metric tons) of chlorinated pesticides were used annually in India and DDT accounted for 40% of this group. Among the HCH isomers, a-HCH is more likely to diffuse into the air and get transported for a long distance, while b-HCH is more resistant to hydrolysis and environmental degradation, and is the predominant isomer in the water, fluids, animal tissues and sediments (Sujatha et al, 1993;Walker et al, 1999;Lee et al, 2001). In the present research work, total HCH concentration of 423 ng/g was detected in the entire study area during 2009.…”
Section: Introductionmentioning
confidence: 48%
“…An approach based on the analysis of OCI residues in sediments collected over a considerable time period can provide a clue for a change in environment and such studies are limited. A few reports are available on the residue analysis of conservative pesticides in CES (Sujatha and Chacko, 1991;Sujatha et al, 1993Sujatha et al, , 1994Sujatha et al, , 1999 but no studies concerning these persistent contaminants in sediment were reported. A broad spectrum of pesticides is used in India for agriculture as well as vector control programs and hence the impact of residues of these OCs on Indian coastal environments is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of industrial units are situated on banks of the Periyar river, and hence the northern part of the estuary receives large quantities of treated and untreated industrial effluents. More details on the environmental setting of this tropical shallow estuary are available elsewhere [8][9][10][11].…”
Section: Methodsmentioning
confidence: 99%